Festivities, Ceremonies, and Rituals in the Lands of the Bohemian Crown in the Late Middle Ages - Nodl, Martin, 1968-; Šmahel, František, 1934-2025; Žůrek, Václav, 1981- (East Central and Eastern Europe in the Middle Ages, 450-1450 ;, 2022)
This book deals with various examples and aspects of rituals and ceremonies in the late medieval Bohemian lands. The individual contributions explore particular rituals (coronation, wedding, funeral) or environments (cities, nobility, court, church).